Social and moral norm differences among Portuguese 1st and 6th year medical students towards their intention to comply with hand hygiene - Roberto, M.S.; Mearns, K.; Silva, S.A. (Psychology, Health and Medicine, 2012)
This study examines social and moral norms towards the intention to comply with hand hygiene among Portuguese medical students from 1st and 6th years (N = 175; 121 from the 1st year, 54 from the 6th year). The study extended the Theory of Planned Behaviour theoretical principles and hypothesised that both subjective and moral norms will be the best predictors of 1st and 6th year medical students' intention to comply with hand hygiene; however, these predictors ability to explain intention variance will change according to medical students' school year. Results indicated that the subjective norm, whose referent focuses on professors, is a relevant predictor of 1st year medical students' intention, while the subjective norm that emphasises the relevance of colleagues predicts the intentions of medical students from the 6th year. In terms of the moral norm, 6th year students' intention is better predicted by a norm that interferes with compliance; whereas intentions from 1st year students are better predicted by a norm that favours compliance. Implications of the findings highlight the importance of role models and mentors as key factors in teaching hand hygiene in medical undergraduate curricula.